STRATEGI KEPALA SEKOLAH DALAM IMPLEMENTASI PPDB DARING (ONLINE) DI SMA MUHAMMADIYAH PANGKALPINANG - Handika Yuda Saputra; Dian Hidayati (Manajemen Pendidikan, 2023)
This study explains how school leadership is carried out in the online PPDB system at SMA Muhammadiyah Pangkalpinang. The purpose of this writing is to find out the principal's leadership strategy in implementing PPDB online. This research method is a type of qualitative research with a descriptive approach. The results of this study show that there are several gaps that occur due to unsynchronization between schools and the bureaucracy. This gap must be able to be overcome by the school principal through his leadership in carrying out existing strategies so that whatever the conditions are, schools are required to be able to survive and implement the existing PPDB Strategy properly and use good facilities and supporting instruments in order to add to the perfection of the PPDB process at SMA Muhammadiyah Pangkalpinang.